Harmoni Ekologis dalam Pengelolaan Sampah untuk Pelestarian Lingkungan di Desa Cangkring, Kecamatan Karanganyar, Kabupaten Demak - Safrizal; Syukriyadin; Syahrizal; Alfisyahrin; Heltha, Fahri (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2024)
In an era increasingly filled with climate change and environmental damage, village garbage management has emerged as one of the significant challenges to overcome. This article describes environmental conservation efforts through wise waste management practices in Cangkring Village, Karanganyar Subdistrict, Demak Regency. Ecological harmony is the foundation, reminding us of the importance of maintaining a balance between human activity and nature. Waste management in villages is not only about reducing the negative impact on the environment but also about creating a balanced relationship between man and nature. In order to preserve the environment in Cangkring village, some efforts have been made to provide trash drums as a waste disposal medium and a banner to the Cangkring village community to dispose of the garbage at its place. The garbage is then processed at a disposal site so that the result can be utilized.